2017
DOI: 10.5038/2375-0901.20.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Factors of Rail Transit Service Quality: An Empirical Analysis for Istanbul

Abstract: Providing a high quality of service in public transportation is essential to reduce dissatisfactions stemming from traffic congestion and noise. Public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
0
7
0
3
Order By: Relevance
“…Machado-León et al (2017) accentuated the role of availability, accessibility, information, time, comfort, and safety in service quality. Isikli et al (2017) found waiting time, crowdedness in cars, and fare as important dimensions of rail transit service quality.…”
Section: Service Quality Customer Satisfaction and Reuse Intention In Public Transportationmentioning
confidence: 99%
“…Machado-León et al (2017) accentuated the role of availability, accessibility, information, time, comfort, and safety in service quality. Isikli et al (2017) found waiting time, crowdedness in cars, and fare as important dimensions of rail transit service quality.…”
Section: Service Quality Customer Satisfaction and Reuse Intention In Public Transportationmentioning
confidence: 99%
“…Keberhasilan dan pertumbuhan pangsa pasar operator angkutan umum sangat ditentukan oleh kualitas layanan yang disediakan, dan terlebih lagi oleh persepsi penumpang pada kualitas yang disediakan (Dragu, Roman & Roman 2013). Kualitas layanan dari perusahaan transportasi yang di antaranya juga dapat meliputi lengkapnya ketersediaan layanan transit, baiknya pemantauan layanan, efisiennya waktu tempuh, terpenuhinya keselamatan dan keamanan, terjaganya kebersihan dan kenyamanan, diperolehnya informasi yang lengkap, serta personel yang baik ISSN: 2715-0186 (Eboli & Mazzulla 2021;Isikli et al, 2017;Machado-León et al, 2017;de Oña et al, 2016) menjadi pendorong munculnya kepuasan pada penumpang. Dalam artian bahwa terdapat hubungan yang sifatnya searah dari karakteristik-karakteristik layanan dalam kualitas layanan terhadap pembentukan kepuasan pelanggan atau penumpang.…”
Section: B Literature Reviewunclassified
“…Customer satisfaction merupakan salah satu implikasi terpenting bagi berbagai bisnis organisasi, yang telah didukung oleh filosofi yang berfokus pada pelanggan perbaikan terusmenerus (Isikli et al, 2017). Customer satisfaction adalah hasil pembelian barang atau jasa konsumen yang dihasilkan dari membandingkan pendapatan dan biaya pembelian dengan hasil yang diharapkan.…”
Section: Kajian Pustaka/literature Review Customer Satisfactionunclassified